2021
DOI: 10.1016/j.yebeh.2019.106556
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted EEG diagnostic review for idiopathic generalized epilepsy

Abstract: Epilepsy diagnosis can be costly, time-consuming and not uncommonly inaccurate. The reference standard diagnostic monitoring is continuous video-EEG monitoring, ideally capturing all events or concordant interictal discharges. Automating EEG data review would save time and resources, thus enabling more people to receive reference standard monitoring and also potentially herald a more quantitative approach to therapeutic outcomes. There is substantial research into automated detection of seizures and epileptic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…With an algorithm developed using ML, the multimodal WD detected GTCS with high sensitivity (92%-100%) and low false alarm rate (0.2-1/day), in phase 2 studies. 42 In the diagnostic space, ML approaches can expedite clinical review of diagnostic scalp EEG, [43][44][45] although currently there are relatively few approved algorithms for automated EEG review. 14 ML has also been extensively applied to the problem of seizure forecasting.…”
Section: S119mentioning
confidence: 99%
“…With an algorithm developed using ML, the multimodal WD detected GTCS with high sensitivity (92%-100%) and low false alarm rate (0.2-1/day), in phase 2 studies. 42 In the diagnostic space, ML approaches can expedite clinical review of diagnostic scalp EEG, [43][44][45] although currently there are relatively few approved algorithms for automated EEG review. 14 ML has also been extensively applied to the problem of seizure forecasting.…”
Section: S119mentioning
confidence: 99%
“…The cloud environment enables collaboration, curation, and new research, such as the development of machine tools. 15…”
Section: Hvet and Researchmentioning
confidence: 99%
“…For example, we found that nonepileptic seizures had a significantly shorter duration at home compared to the hospital setting (mean = 320 seconds at home vs mean = 868 seconds in the hospital, unpublished data from King's College Hospital). The cloud environment enables collaboration, curation, and new research, such as the development of machine tools 15 Current challenges and limitations …”
Section: Current Service Models For Hvetmentioning
confidence: 99%
“…Our first contribution in this paper, is the evaluation of the performance of the classifier in case that the EEG segments for which the classifier is least confident are deferred to a human annotator, who is assumed to annotate perfectly. A similar scenario is quite common in clinical epilepsy research: the algorithm flags all suspicious activity, which is then presented to a human annotator [25]. Learning algorithms with a reject option have a long history in machine learning research [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Application of this approach to seizure detection has been limited. Computer-assisted detection of epileptic discharges from full scalp EEG has been investigated by Clarke et al [25]. On a retrospective dataset, a neural network achieved a DS of 96.7% with 1670 false detections per 24 h. They employed this model in a clinical application of ambulatory measurement of 7 patients with idiopathic generalised epilepsy.…”
Section: Introductionmentioning
confidence: 99%